Assessment of Pain and Activity Using an Electronic Pain Diary and Actigraphy Device in a Randomized, Placebo‐Controlled Crossover Trial of Celecoxib in Osteoarthritis of the Knee. Issue 3 (5th February 2014) - Trudeau, Jeremiah; Van Inwegen, Richard; Eaton, Thomas; Bhat, Gajanan; Paillard, Florence; Ng, Dik; Tan, Keith; Katz, Nathaniel P.
Abstract Objective The primary goal was to determine whether a composite measure of pain and activity is a more responsive assessment of analgesic effect than pain alone or activity alone in patients with osteoarthritis (OA) of the knee. Design We conducted a randomized, double‐blind, placebo‐controlled, 2‐period, crossover study of celecoxib vs. placebo in subjects with chronic pain due to knee OA. Patients with knee OA and baseline pain intensity score ≥4 on a 0–10 numerical rating scale (NRS) before each period were randomized. Pain endpoints included in‐clinic pain score (24‐hour and 1‐week recall), daily paper diary pain score, current pain on an electronic pain diary (each on NRS), and WOMAC pain subscale. Activity measures included WOMAC function subscale and actigraphy using a device. Three composite pain–activity measures were prespecified. Results Sixty‐three patients were randomized and 47 completed the study. The WOMAC pain subscale was the most responsive of all five pain measures. Pain–activity composites resulted in a statistically significant difference between celecoxib and placebo but were not more responsive than pain measures alone. However, a composite responder defined as having 20% improvement in pain or 10% improvement in activity yielded much larger differences between celecoxib and placebo than with pain scores alone. Actigraphy was more responsive than the WOMAC function scale, possibly due to lower placebo responsiveness. Conclusion We have identified composite pain–activity measures that are similarly or more responsive than pain‐alone measures in patients with OA. Further research is warranted to determine the optimal method for computing these composites.